2011
DOI: 10.1074/jbc.m111.263780
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Novel Ssl0352 Protein (NdhS), Essential for Efficient Operation of Cyclic Electron Transport around Photosystem I, in NADPH:plastoquinone Oxidoreductase (NDH-1) Complexes of Synechocystis sp. PCC 6803

Abstract: Background: Multisubunit NDH-1 complexes of cyanobacterial are involved in CO 2 uptake and cyclic electron transfer (CET). Result: Ssl0352, a small unknown protein of Synechocystis 6803, is tightly associated with NDH-1. Deletion of ssl0352 impairs CET but not the NDH-1 assembly. Conclusion: Ssl0352 is a novel NDH-1 subunit, NdhS. Significance: NdhS is important for the function of NDH-1 complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 56 publications
(55 reference statements)
2
73
0
Order By: Relevance
“…All genes ( ndhA-C, E, G-K, M-N, S ), encoding NDH-1 core subunits (30,31), except ndhO , were downregulated in ΔrpoZ (Supplementary Table S2), and downregulation at protein level was verified for the NdhJ and NdhK proteins (Figure 3B). The ndhF4 and ndhD4 genes (but not cupB ) for the CO 2 uptake form of NDH-1 were downregulated, and also the other constitutively expressed low-affinity inorganic carbon transporter system, encoded by the bicA gene, was down.…”
Section: Resultsmentioning
confidence: 88%
“…All genes ( ndhA-C, E, G-K, M-N, S ), encoding NDH-1 core subunits (30,31), except ndhO , were downregulated in ΔrpoZ (Supplementary Table S2), and downregulation at protein level was verified for the NdhJ and NdhK proteins (Figure 3B). The ndhF4 and ndhD4 genes (but not cupB ) for the CO 2 uptake form of NDH-1 were downregulated, and also the other constitutively expressed low-affinity inorganic carbon transporter system, encoded by the bicA gene, was down.…”
Section: Resultsmentioning
confidence: 88%
“…The active NDH also contained NdhS (Fig. 1), the new subunit of NDH identified in Arabidopsis thaliana [18]and in Synechocystis 6803 [19] responding to the activity of NDH pathway. According to the structure similarity of NdhS with PsaE, the authors suggested that NdhS might bind with Fd which might be an electron donor for NDH.…”
Section: Discussionmentioning
confidence: 96%
“…Cyanobacterial NADPH dehydrogenase (NDH-1) complexes localize in the thylakoid membrane (Ohkawa et al, 2001(Ohkawa et al, , 2002Zhang et al, 2004;Xu et al, 2008;Battchikova et al, 2011a) and participate in a variety of bioenergetic reactions, including respiration, cyclic electron transport around photosystem I, and CO 2 acquisition (Ogawa, 1991;Mi et al, 1992;Ohkawa et al, 2000). Structurally, the cyanobacterial NDH-1 complexes closely resemble energyconverting Complex I in eubacteria and the mitochondrial respiratory chain despite the absence in cyanobacterial genomes of homologs of the three subunits that constitute the catalytically active core of Complex I (Friedrich et al, 1995;Friedrich and Scheide, 2000;Arteni et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…NDH-CET allows optimal functioning of photosynthesis by increasing the pH gradient and supplying additional ATP for CO 2 assimilation. This function is particularly important under environmental stress conditions, such as high light (Endo et al, 1999;Battchikova et al, 2011a), in which the ATP demand is greatly increased. Moreover, the impairment of cyanobacterial NDH-CET caused by mutation of some auxiliary factors for NDH-1 complexes and Ndh subunits, such as NdhS (Battchikova et al, 2011a), results in high light-sensitive growth phenotypes.…”
Section: Introductionmentioning
confidence: 99%